2021
DOI: 10.5194/acp-21-15783-2021
|View full text |Cite
|
Sign up to set email alerts
|

The unexpected smoke layer in the High Arctic winter stratosphere during MOSAiC 2019–2020

Abstract: Abstract. During the 1-year MOSAiC (Multidisciplinary drifting Observatory for the Study of Arctic Climate) expedition, the German icebreaker Polarstern drifted through Arctic Ocean ice from October 2019 to May 2020, mainly at latitudes between 85 and 88.5∘ N. A multiwavelength polarization Raman lidar was operated on board the research vessel and continuously monitored aerosol and cloud layers up to a height of 30 km. During our mission, we expected to observe a thin residual volcanic aerosol layer in the str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
182
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(195 citation statements)
references
References 102 publications
12
182
1
Order By: Relevance
“…However, Haarig et al (2018) and Ohneiser et al (2020) showed that pronounced smoke layers (linked to pyroCb activity) frequently produce depolarization ratios even > 0.15 at 532 nm. On the other hand, Ohneiser et al (2021) reported smoke layers over the high Arctic showing values of PDR532 of 0.02-0.03. So, stratospheric smoke can obviously show rather different depolarization ratio values.…”
Section: Calipso Aerosol Typing In the Case Of Stratospheric Aerosolmentioning
confidence: 98%
See 4 more Smart Citations
“…However, Haarig et al (2018) and Ohneiser et al (2020) showed that pronounced smoke layers (linked to pyroCb activity) frequently produce depolarization ratios even > 0.15 at 532 nm. On the other hand, Ohneiser et al (2021) reported smoke layers over the high Arctic showing values of PDR532 of 0.02-0.03. So, stratospheric smoke can obviously show rather different depolarization ratio values.…”
Section: Calipso Aerosol Typing In the Case Of Stratospheric Aerosolmentioning
confidence: 98%
“…The Raman lidar technique allows us to independently determined the particle backscatter coefficients at 355 and 532 nm (from the ratio of the total to the respective nitrogen Raman signal) and the particle extinction coefficient at 355 and 532 nm (from the 387 and 607 nm nitrogen Raman signal profiles), and thus, to obtain observed values for the extinction-to-backscatter ratio at these two wavelengths (Ansmann et al, 1992). The latest status of the computation of backscatter and extinction coefficients and lidar ratios at 355 and 532 nm for stratospheric smoke is explained in detail in Haarig et al (2018) and Ohneiser et al (2020), Ohneiser et al (2021). Many measurement examples for Canadian, Australian, and Siberian smoke are shown in these publications.…”
Section: Caliop Vs Polly: Different Aerosol Typing Optionsmentioning
confidence: 99%
See 3 more Smart Citations